Study of Janus Amphiphilic Graphene Oxide as a High-Performance Shale Inhibitor and Its Inhibition Mechanism - Lv, Kaihe; Huang, Pan; Zhou, Zhishi; Wei, Xin; Luo, Qi; Huang, Ziming; Yan, Hui; Jia, Han (Frontiers in Chemistry, 2020)
The Janus amphiphilic graphene oxide (JAGO) modified by the dodecylamine in one side of graphene oxide (GO) was investigated for its novel use as a shale inhibitor. JAGO was synthesized through the pickering emulsion template technology and was characterized by Fourier-transform infrared spectra, UV-vis spectra and transmission electron microscopy. Compared with potassium chloride (5%), polyether diamine (2%), and the pristine GO (0.2%), the highest shale recovery rate (75.2% at 80 °C) and the lowest swelling height of Mt-pellets (2.55 mm) in JAGO (0.2%) demonstrated the excellent inhibitive property of JAGO. Furthermore, JAGO also greatly reduced the filtration loss as a perfect plugging agent. Based on the results of X-ray diffraction, contact angle measurements and pressure transmission tests, we proposed that the 2D nano-sheet amphiphilic structure of JAGO, which enable JAGO to be effective both in chemical inhibition and physical plugging, was responsible for its remarkable inhibition performances.